Dr. Josh DeSerres — Deep Plane Facelift — Edmonton - DeSerres, Josh (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Josh DeSerres, practicing in Edmonton, Canada. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003168; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; canada; edmonton